2016
DOI: 10.1016/j.petrol.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and rheological properties of API bentonite drilling fluid: pH effect, yield stress, zeta potential and ageing behaviour

Abstract: API bentonite, a key ingredient of drilling muds, displayed a negative zeta potential across the whole pH range of 2.5 to 12.3. It contained two very rheological active ingredients, sodium montmorillonite or Na+Mt (40.4%) and needle-shape sepiolite (16%). Due to the interplay of these two ingredients, the rheological behaviour displayed by the API bentonite suspensions is quite different to other bentonite suspensions. The gel displayed a very low or no yield stress at low acidic pH and a maximum yield stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 55 publications
1
23
0
2
Order By: Relevance
“…Kanna et al [33] studied the effect of bentonite and other mud additives on the mud optimum design in terms of mud rheology, pH value, and filtration properties. Huang et al [34] showed that API Bentonite slurries displayed unusual rheology at low pH. The drilling fluid yield stress and viscosity had low values at low pH, and maximum yield stress and viscosity was found to be at pH 9.…”
Section: Effect Of Bentonite On Mud Rheologymentioning
confidence: 99%
“…Kanna et al [33] studied the effect of bentonite and other mud additives on the mud optimum design in terms of mud rheology, pH value, and filtration properties. Huang et al [34] showed that API Bentonite slurries displayed unusual rheology at low pH. The drilling fluid yield stress and viscosity had low values at low pH, and maximum yield stress and viscosity was found to be at pH 9.…”
Section: Effect Of Bentonite On Mud Rheologymentioning
confidence: 99%
“…Moreover, a lesser volume of filtrate ensures the formation of a thin, impermeable filter cake drastically reducing the chances of differential pipe sticking. A lesser pH means an increased amount of additives to achieve the right viscosity (Huang et al 2016;Saboori et al 2018). Hence, an optimum pH range ensures savings of the additives and operation costing.…”
Section: The Ph Of Resulting Formulationsmentioning
confidence: 99%
“…The properties of mud are highly dependent on shear history and temperature; hence, it is of utmost significance to test the proposed mud cake composition in the laboratory prevailing the circumstances comparable to drilling a well. Many drilling mud additives degrade at high temperatures (Huang et al 2016;Hamad et al 2020). Consequently, the 250-297 Barite + XCP + husk 4 Water: 500 ml, barite: 110 g, XCP: 2 g, Husk: 4 g effect of temperature should be observed in all drilling fluid components and additives to corroborate their efficiency.…”
Section: Data Interpretationmentioning
confidence: 95%
See 1 more Smart Citation
“…The suspension of these two ingredients showed a very low or no yield stress at acid pH and approached the maximum value of pH 8-12. Because the magnesium is released from sepiolite at low pH, its hydrolysis products are formed and adsorbed on particle surfaces gradually with the increase of the pH value [10]. The acid-base environment shows a significant influence on the rheological properties of montmorillonite suspension.…”
Section: Introductionmentioning
confidence: 99%